Poster Abstract: UWB Ranging with Scheduled Broken Packet Reception - Tileutay, Laura; Park, Jiwoong; Ko, Young Bae (Proceedings - 23rd ACM/IEEE International Conference on Information Processing in Sensor Networks, IPSN 2024, 2024)
Ultra-wideband technology has the potential to provide precise real-world localization. However, due to Non-Line-of-Sight propagation, the transmitted packet can be incomplete or lost during the ranging, which may lead to communication failure. To minimize this, we propose the scheduled signal reception technique. The proposed approach is tested in a real-world environment with Qorvo DWM3001C modules. The experimental results verify its efficiency, offering a practical solution for UWB-based localization, particularly in dynamic circumstances.
Keywords: Communication failure; Localisation; Non-line-of-sight propagation; Packet reception; Preamble detection; Real world environments; Real-world; Signal reception; Ultra-wideband technology; Ultrawide band; Localization; Preamble detection; Ultra-Wideband